2021
DOI: 10.3389/fpsyg.2021.647821
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Psychological Distress Among Pakistani Adults During the COVID-19 Outbreak: Parallel and Serial Mediation Analyses

Abstract: Objective: The global outbreak of COVID-19 has greatly affected individual's lives around the world and resulted in various negative psychological consequences. During the pandemic, reflection on and attention to COVID-19 may help in dealing with its symptomology but frequent and persistent thoughts about the situation can be unhealthy. The present study examined the direct and indirect associations between obsession concerning COVID-19, psychological distress, life satisfaction, and meaning in life.Design: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Surprisingly, consuming healthy, eco-friendly, and sustainable products reduces PD ( Kushwah et al, 2019 ). In addition to this, the studies have found that PD and MS increase the effect of FCV ( Menzies and Menzies, 2020 ; Ashraf et al, 2021 ), and they impact the purchase behavior of consumers. Still, fewer have investigated the mediation of MS and PD between the FCV and GPB.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, consuming healthy, eco-friendly, and sustainable products reduces PD ( Kushwah et al, 2019 ). In addition to this, the studies have found that PD and MS increase the effect of FCV ( Menzies and Menzies, 2020 ; Ashraf et al, 2021 ), and they impact the purchase behavior of consumers. Still, fewer have investigated the mediation of MS and PD between the FCV and GPB.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 92%
“…Researchers have found that PD significantly impacts an individual’s health, and sometimes they find coping strategies to reduce the distress. A study conducted by Ashraf et al (2021) found that searching for meaning in life and feeling satisfied may reduce PD.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As in the rest of the world, COVID-19 had a similar impact on mental health in Pakistan with an increase in the average level of stress, anxiety and depression 69. The COVID-19 pandemic also had a negative impact on mental health issues such as grief, helplessness, psychological distress, shame, post-traumatic symptoms, anger, stigma, depression, panic attacks, anxiety, loneliness, fear and anger 71 72. Community living depends on family interaction, social support and cultural activities to keep people busy and happy.…”
Section: Mental Health In Pakistanmentioning
confidence: 99%
“…In times of crisis, meaningfulness is a resource that fundamentally determines whether a person sees their life as worth living and is therefore willing and motivated to actively overcome challenges and take responsibility for their health [20]. Various studies have shown that meaning in life was a protective factor during the pandemic [2,[23][24][25][26]. At the same time, it emerged that for quite a few people, the large-scale crisis was accompanied by a shaking of their worldview [27].…”
Section: Introductionmentioning
confidence: 99%